2019
DOI: 10.23917/jiti.v18i2.7826
|View full text |Cite
|
Sign up to set email alerts
|

A Literature Review on Green Supply Chain Management Adoption Drivers

Abstract: This article provides a systematic literature review of the driving factors influencing the application of green supply chain management (GSCM). The GSCM adoption issues have been widely given attention by researchers and practitioners since the adoption of GSCM would impact significantly on an organization's environmental, social, and financial performance. Most GSCM adoption has been discussed in the perspective of logistics management activities such as procurement, manufacturing, transportation, and revers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…In reality, green procurement has been addressed and supported in many industrialized and developing nations during the past few years. Two sorts of variables influence the adoption of green procurement: internal and external (Masudin, 2019). Studies have found that organizational elements are internal drivers, whereas various factors, including rules, consumers, competition, and society, are external drivers (Rane & Thakker, 2020).…”
Section: Low-carbon Logisticsmentioning
confidence: 99%
“…In reality, green procurement has been addressed and supported in many industrialized and developing nations during the past few years. Two sorts of variables influence the adoption of green procurement: internal and external (Masudin, 2019). Studies have found that organizational elements are internal drivers, whereas various factors, including rules, consumers, competition, and society, are external drivers (Rane & Thakker, 2020).…”
Section: Low-carbon Logisticsmentioning
confidence: 99%
“…Pressure from government agencies and national/international regulators influences responsible environmental behavior [69,70]. Public awareness of the company's environmental activities is the most effective motivating factor that is identified by the company when making green decisions [71]. If companies have a legal concern for the environment and there is social approval, environmental measures will be implemented more rapidly throughout the supply chain.…”
Section: Gscmentioning
confidence: 99%
“…This term has its origins in the mid-1970s and became more relevant from the 1980s. [23]. The traditional SC is defined as an integrated manufacturing process wherein raw materials are manufactured into final products before delivering to customers with intermediaries, sellers of both [31].…”
Section: Green Supply Chain Managementmentioning
confidence: 99%
“…Nowadays, we are talking about Green Supply Chain Management (GSCM) since "there is a growing need for integrating environmentally sound choices into supply-chain management research and practice" [3] (p. 53). In spite of reasons to add "green" to business, policies are further analysed, and in a subsequent part of this study, it is convenient to comment that motives of this evolution are basically the increasing deterioration of the environment [3,31,51] and the social and legal pressures [23,31,44,52]. The literature also analyses stakeholders' influence on SCM [53,54].…”
Section: Green Supply Chain Managementmentioning
confidence: 99%
See 1 more Smart Citation